2001
DOI: 10.1081/css-100104117
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Remote Sensing Techniques to Increase Nitrogen Use Efficiency of Corn

Abstract: Nitrogen (N) fertilizer recommendations made without adequate knowledge of the N supply capability of a soil can lead to inefficient use of N. Proper crediting of N from manure and legumes as well as mineralization of N from organic matter is difficult. Remote sensing techniques that use the crop to indicate its N status show considerable promise for improving N management. Objectives of this paper were twofold: 1) to compare the N Reflectance Index (NRI) calculated from ground-based radiometer measurements ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 10 publications
1
37
0
1
Order By: Relevance
“…The NRI was highly correlated with an N sufficiency index calculated from SPAD chlorophyll meter data and provided a rapid assessment of corn plant N status for mapping purposes. A more recent study using the NRI to monitor in-season plant N resulted in reducing applied N using fertigation by 39 kg N ha Ϫ1 without reducing grain yield (Bausch and Diker, 2001). Because this index was based on the plant canopy as opposed to the individual leaf measurements obtained with SPAD readings, it has potential for larger scale applications and direct input into variable rate fertilizer application technology.…”
Section: Nitrogenmentioning
confidence: 99%
See 1 more Smart Citation
“…The NRI was highly correlated with an N sufficiency index calculated from SPAD chlorophyll meter data and provided a rapid assessment of corn plant N status for mapping purposes. A more recent study using the NRI to monitor in-season plant N resulted in reducing applied N using fertigation by 39 kg N ha Ϫ1 without reducing grain yield (Bausch and Diker, 2001). Because this index was based on the plant canopy as opposed to the individual leaf measurements obtained with SPAD readings, it has potential for larger scale applications and direct input into variable rate fertilizer application technology.…”
Section: Nitrogenmentioning
confidence: 99%
“…In practice, however, the seedling plants are usually too small and their signal is overwhelmed by that of the soil. Acquiring imagery very early in the day (i.e., large solar zeniths) or with off-nadir viewing angles offers a potential solution to plant detection at low leaf area levels (Pinter et al, 1983b;Bausch and Diker, 2001). As more sensitive sensors are deployed and techniques for calibration and removing effects of changes in soil background improve p.…”
Section: Photogrammetric Engineering and Remote Sensingmentioning
confidence: 99%
“…In both systems, a small N application via irrigation water is triggered whenever relative reflectance/transmittance falls below 0.95 of the value observed in a non-N-limited reference area. This system has produced numerous positive outcomes (Bausch and Diker, 2001;Bausch and Delgado, 2003) but is limited in application to irrigated fields with the capability to add N to irrigation water. This limitation was removed by Varvel et al (2007) by developing chlorophyll meter interpretations that produce a rate recommendation for a one-time application, which became the basis for the reflectance sensor interpretations developed by Solari et al (2010).…”
Section: Sensing Spectral Properties For Nitrogen Recommendations Formentioning
confidence: 99%
“…Confounding effects can originate from changes in canopy architecture, i.e. leaf rolling and leaf angle (Moran et al 1989), reflectance coming from the bare soil (Bausch 1993;Clarke et al 2001), and probably from changes in properties of leaf surfaces (Chaves et al 2003). It has been suggested that measuring the proportion of the targetted component (i.e.…”
Section: Remote Sensing Of Nitrogen Deficiencymentioning
confidence: 99%